Using Customized Hangaroo Game for Vocabulary Teaching at SMPN 1 Bosso - Citra Widyastuti; Amalia Yahya; Magfirah Thayyib (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Using game is one of the most fashionable techniques in teaching vocabulary. This research aims to find out whether the customized hangaroo game is effective to improve the students’ vocabulary in the eighth grade of SMPN 1 Bosso. Hangaroo game is customized to be a non-digital/offline game to meet the needs of English vocabulary teaching in that class. This research applied pre-experimental method with pre-test, treatment, and post-test design. The instrument of this research was an objective vocabulary test. The treatment of teaching vocabulary using customized hangaroo game was conducted in five meetings. The data from the tests were analyzed using quantitative procedures including statistical analysis using SPSS 22. The results show that using customized hangaroo game is effective in improving the students’ vocabulary mastery at the eighth grade of SMPN 1 Bosso. The students’ mean score the pre-test was 36.4783 (poor) while in post-test was 51.6957 (fair). From the t-test of the students’ vocabulary, p value was smaller than α (0.00<0.05). The customized hangaroo game could interest and motivate the students in learning vocabulary. It can help the students to develop their spelling and pronunciation. It can also facilitate the students to cooperate in group and share to class.